Association Between Stingless Bees (Apidae, Meliponini) and the Dry Forest Flora in the Northern Region of Guanacaste, Costa Rica - Barquero Elizondo, Ana Isabel (2018)
Stingless bees are important pollinators in tropical and subtropical regions. They are associated with the flora that provides them with food, sites for nesting, resins, sap, and exudates. We sought to determine the association between bees and flora in the Cerro El Hacha sector (intervened primary forest) and the Pocosol sector (secondary forest) of the Guanacaste National Park, where the nests were inventoried in 33 plots of 20 x 20 m². Pollen from plants was collected within the plots and around the nests (radius 500 m). Corbicular charges of pollen were, also, collected and analyzed; they came from bees trapped with entomological nets at the entrance of the nests. In the Cerro El Hacha sector, pollen was collected from three nests of Scaptotrigona pectoralis, and in the Pocosol sector pollen from was collected from two nests of Trigona fulviventris. A density of 4.43 nests / ha-1 was obtained from these species: Tetragonisca angustula, Tetragona ziegleri, Plebeia frontalis, and Trigona fulviventris. The nests were found in the trunks of trees, with a preference for Quercus oleoides, where 50 % of them were found. The food plants used by S. pectoralis in Cerro El Hacha were the following: Cupania guatemalensis (30 %), Byrsonima crassifolia (21 %), and Cedrela odorata (15 %). While for T. fulviventris in the Pocosol sector, the most important plants were Baltimora recta (26 %), Dorstenia contrajerva (9 %), and Desmodium sp. (9 %). The important role played by the tree species Quercus oleoides for the conservation of the populations of these insects is evident.